T.H. Green ethics, metaphysics, and political philosophy - Dimova-Cookson, Maria, 1967-; Mander, W. J. (Oxford : Clarendon, 2006)
This volume offers a collection of essays that introduce and critically examine the great English idealist thinker T.H. Green's ideas both in their context and in their relevance to contemporary debates.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Green, Thomas Hill, -- 1836-1882.; Ethics; Metaphysics; Political science -- Philosophy